PENGARUH BIMBINGAN KELOMPOK TERHADAP PENYESUAIAN SOSIAL SISWA SMP NEGERI 7 TAMBANG - Rio Sardi; Zulfan Saam; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of group guidance on social adjustment of class VII students of State Junior High School 7 Tambang academic year 2018/2019. This research was conducted in SMP Negeri 7 Tambang from August 2018 to October 2018. The research method used was the experimental method of the one group pattern. The research subjects in this study were Grade VII students of SMP Negeri 7 Tambang with a low level of social adjustment. The instrument of data collection used is a questionnaire using a modified Likert scale. The data analysis technique used is non parametric correlation statistical technique. Based on the results of the Spearman rank correlation it can be concluded that the group guidance relationship with student adjustments is in the strong category of 0.793 with a percentage of 79.3%. then to find out the coefficient of determination as follows: (rs) 2 = (0.793) 2 = 0.629, This means that the influence of group guidance techniques on students' social adjustment is 62.9%. So that group guidance can be said to be very effective in reducing the level of social adjustment of SMP Negeri 7 Tambang students. While 62.9% is influenced by other factors that come from within or from the student's environment. There are differences in the level of social adjustment of students before and after the implementation of group guidance. the level of social adjustment of students prior to group guidance was 10% in the High category and 90% in the low category. After group guidance the level of social adjustment of students after group guidance was 85% in the very high category and 15% in the high category.Keywords: Group Guidance, Social Adjustment